2016
DOI: 10.1177/1471301215601619
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative assessment of self-identity in people with advanced dementia

Abstract: This study aimed to understand the preserved elements of self-identity in persons with moderate to severe dementia attributable to Alzheimer's disease. A semi-structured interview was developed to explore the narrative self among residents with dementia in a residential care facility, and residents without dementia in an independent living setting. The interviews were transcribed verbatim from audio recordings and analyzed for common themes, while being sensitive to possible differences between the groups. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 16 publications
4
12
0
Order By: Relevance
“…This study found consensus on the core elements of personhood incorporating: interests and preferences; lifecourse experiences; social interaction; family; and place. The findings reflect both theoretical and empirical evidence on the self (Sabat and Harré, 1992;Sabat and Collins, 1999;Batra et al, 2016) and on relational personhood (Kitwood, 1997;Nowell et al, 2013;Borley and Hardy, 2017), including familial roles (Cohen-Mansfield et al, 2006). This study provides further support for the inclusion of these core elements into person-centred care models (Brooker, 2007;Fazio et al, 2018).…”
Section: Discussionsupporting
confidence: 76%
“…This study found consensus on the core elements of personhood incorporating: interests and preferences; lifecourse experiences; social interaction; family; and place. The findings reflect both theoretical and empirical evidence on the self (Sabat and Harré, 1992;Sabat and Collins, 1999;Batra et al, 2016) and on relational personhood (Kitwood, 1997;Nowell et al, 2013;Borley and Hardy, 2017), including familial roles (Cohen-Mansfield et al, 2006). This study provides further support for the inclusion of these core elements into person-centred care models (Brooker, 2007;Fazio et al, 2018).…”
Section: Discussionsupporting
confidence: 76%
“…Research has shown that the Self 1 is preserved among persons with advanced dementia. Even when they almost entirely answer "yes" or "no" to questions, they still show that they can experience themselves as "I" (32,60). Still it seems reasonable to suggest that we can help persons preserve their feeling of being an I by making them feel that they are seen and listened to, that is that they are.…”
Section: Strengthening Self 1 Communionmentioning
confidence: 99%
“…Studies based on the Harré-Sabat theory of selfhood have shown that among persons with mild to moderate dementia, Self 1 was not affected during the course of dementia, whereas Selves 2 and 3 were (13)(14)(15). A few studies using that theory concern persons with advanced dementia (e.g., 24,[31][32][33]. Studies that do not use the Harré-Sabat theory have found that some aspects of sense of self were preserved while other aspects were reduced among persons with advanced dementia (e.g., [34][35][36][37].…”
Section: Selfhoodmentioning
confidence: 99%
“…To be respected and seen by others as capable human beings are of the highest importance for all humans, as described in theories of PCC by Kitwood (1997). He further described that this is particularly important in the context of dementia because personal interactions may help or hinder a person's desire to maintain identity despite increasing cognitive impairment, which was also discussed in previous studies focussing on the identity of people with dementia (Batra et al, 2016;Brown Wilson, 2017;Hedman et al, 2018).…”
Section: Discussionmentioning
confidence: 90%